Sublevação e manifestação da vontade destituinte: contribuições à teoria do poder constituinte a partir de Michel Foucault - Lorena Martoni de Freitas (2021)
This work seeks to critically rethink the theme of the double dimension of constituent power, based on the political philosophy of Michel Foucault. Starting from the assumption that no social order emerges ex nihilo in a space previously marked by anomie, the constituent power is taken here as a movement that is not only productive but also disruptive, which involves the rejection of a previous rule of authority as a condition for the emergence of a new normative organization. In these terms, it is a phenomenon of a procedural and bilateral nature, so we must take it as a diffuse daily exercise that includes both a dis-constituent and a re-constituent dimension. However, more and more constitutional studies have treated the issue of constituent power as a mere question of the historical principle of the legal order that, from a teleological perspective of history, is absorbed by the constituted power once the so-called democratic structures of the current rule of law are consolidated. In order to guarantee the permanence of fundamental rights and the stability of democratic institutions – especially after the totalitarian experiences that marked the last century –, the disconstituent dimension of the constituent power has been gradually silenced. However, this theoretical trend has faced serious challenges due to the new social movements that have taken the streets in various parts of the globe in recent decades, thereby generating a internal crisis on the constituent power theory. Faced with this crisis, a new approach started to be configured in the field of constituent power theory, aimed at analyzing in more depth its de-constituent dimension, and which we can gather under the label of “destituent thought”. Within this philosophical field, Michel Foucault appears as an indispensable author, so the aim of this work is to investigate his work in relation to the theme of constituent power and in light of the problems arising within the destituent thought.